Carbon Emission Disclosure in the Energy Sector: Environmental Management System and Environmental Performance - Tasya Kemala Puteri; Wahdan Arum Inawati (Universitas Kristen Maranatha, 2023)
When non-renewable energy sources like coal, oil, and natural gas are burned, extra carbon gas (CO2) is released into the environment. The corporation releases a statement regarding carbon emission disclosure, which is a part of carbon accounting and involves evaluating and lowering carbon emissions from each manufacturing activity. The purpose of the study is to evaluate the simultaneous and partial effects of the environmental management systems, environmental performance, leverage, and firm age control variables on carbon emission disclosure in the energy sector listed on the Indonesia Stock Exchange from 2017 to 2021. Data analysis using panel data regression with the energy sector research population listed on the Indonesia Stock Exchange in 2017 to 2021. There were 10 research sample companies, with 2 companies being outliers, so that 40 samples were obtained with purposive sampling techniques. The test results show that environmental management systems, environmental performance, as well as leverage control variables and firm age have a simultaneous impact. Environmental management system with variable control leverage and firm age have partial positive impact and environmental performance with variable control leverage and firm age has no impact. This research is expected to help company management and investors in making decisions to invest in the energy sector. Keywords: Environmental Management System, Environmental Performance, Carbon Emission Disclosure